Exercise or not? An empirical illustration of the role of behavioral alternatives in exercise motivation and resulting theoretical considerations - Timme, Sinika; Brand, Ralf; Raboldt, Michaela (Frontiers in Psychology, 2023)
Objective Individuals’ decisions to engage in exercise are often the result of in-the-moment choices between exercise and a competing behavioral alternative. The purpose of this study was to investigate processes that occur in-the-moment (i.e., situated processes) when individuals are faced with the choice between exercise and a behavioral alternative during a computerized task. These were analyzed against the background of interindividual differences in individuals’ automatic valuation and controlled evaluation of exercise. Method In a behavioral alternatives task 101 participants were asked whether they would rather choose an exercise option or a behavioral alternative in 25 trials. Participants’ gaze behavior (first gaze and fixations) was recorded using eye-tracking. An exercise-specific affect misattribution procedure (AMP) was used to assess participants’ automatic valuation of exercise before the task. After the task, self-reported feelings towards exercise (controlled evaluation) and usual weekly exercise volume were assessed. Mixed effects models with random effects for subjects and trials were used for data analysis. Results Choosing exercise was positively correlated with individuals’ automatic valuation (r = 0.20, p = 0.05), controlled evaluation (r = 0.58, p < 0.001), and their weekly exercise volume (r = 0.43, p < 0.001). Participants showed no bias in their initial gaze or number of fixations towards the exercise or the non-exercise alternative. However, participants were 1.30 times more likely to fixate on the chosen alternative first and more frequently, but this gaze behavior was not related to individuals’ automatic valuation, controlled evaluation, or weekly exercise volume. Conclusion The results suggest that situated processes arising from defined behavioral alternatives may be independent of individuals’ general preferences. Despite one’s best general intention to exercise more, the choice of a non-exercise alternative behavior may seem more appealing in-the-moment and eventually be chosen. New psychological theories of health behavior change should therefore better consider the role of potentially conflicting alternatives when it comes to initiating physical activity or exercise.